[(x+2013)*2013-2013]/2013=2014
Răspunsuri la întrebare
Răspuns de
3
[(x+2013)*2013-2013]:2013=2014
(x+2013)*2013-2013=2014*2013
(x+2013)*2013=2014*2013+2013
(x+2013)*2013=2013*(2014+1)
(x+2013)*2013=2013*2015
x+2013=2015
x=2015-2013
x=2
(x+2013)*2013-2013=2014*2013
(x+2013)*2013=2014*2013+2013
(x+2013)*2013=2013*(2014+1)
(x+2013)*2013=2013*2015
x+2013=2015
x=2015-2013
x=2
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
10 ani în urmă
Engleza,
10 ani în urmă
Matematică,
10 ani în urmă